Primary therapy of Waldenström's macroglobulinemia with 2-chlorodeoxyadenosine - Dimopoulos, M.A.; Kantarjian, H.; Weber, D.; O'Brien, S.; Estey, E.; Delasalle, K.; Rose, E.; Cabanillas, F.; Keating, M.; Alexanian, R. (Journal of Clinical Oncology, 1994)
Purpose: To assess the activity of 2-chlorodeoxyadenosine (2CdA) as primary therapy for patients with Waldenström's macroglobulinemia. Patients and Methods: 2CdA was given to 26 consecutive, previously untreated and symptomatic patients with Waldenström's macroglobulinemia. Two courses were administered to outpatients at a dose of 0.1 mg/ kg body weight per day for a 7-day continuous infusion using a portable pump through a central venous catheter. Responding patients were followed up without further therapy and were scheduled to receive two additional treatments with 2CdA on disease relapse. Results: Twenty-two of 26 patients responded to the 2CdA therapy (85%; 95% confidence interval [Cl], 65% to 96%), including three patients who achieved a complete response and 19 patients who had a partial response. Treatment was well tolerated, with no acute hematologic toxicity. A marked and sustained reduction of CD4+ lymphocytes occurred in all patients and may have contributed to a fatal infection with disseminated herpes simplex in one patient. With a median follow-up of 13 months, five patients have relapsed and all re-treated patients have responded again to 2CdA. Conclusion: 2CdA is highly active in previously untreated patients with Waldenström's macroglobulinemia. A limited program of treatment induced responses of good quality and long duration in more than 80% of patients. © 1994 by American Society of Clinical Oncology.